Enhancing ESL Students' Academic Writing Skills Through Collaborative Learning. - Kumar, Amit (IUP Journal of English Studies, 2025)
The study examines whether students' academic writing skills can be enhanced through collaborative learning, given the social constructive and sociocultural framework in the ESL context in India. It also intends to discover the developmental process, effectiveness of peer feedback, and students' attitudes and perceptions with regard to developing writing skills in ESL collaborative contexts. Comprising a three-stage research design which involved 48 students of the higher secondary regional medium, the 'pre-intervention' stage of the study aims to understand the existing situation by analyzing the prescribed textbook, administering questionnaires, observing classes, and conducting diagnostic tests and interviews. As the incorporation of collaborative learning involves a process, the second stage, 'during-intervention' was intended to assess the intensive instructional process of academic writing, including an administration of a mid-achievement test. Finally, the 'post-intervention' stage administered an achievement test and perception checklist, followed by semi-structured interviews to discover the effectiveness of collaborative learning. The analysis and interpretation of the data suggested that collaborative learning effectively enhances students' academic writing skills with affirmative perceptions, beliefs, and attitudes. Ultimately, these interpretations have substantial implications for classroom pedagogy, material development, teachers' professional development, and policymaking.